O Brasil na Antártica: A importância científica e geopolítica do PROANTAR no entorno estratégico brasileiro - Israel de Oliveira Andrade; Leonardo Faria de Mattos; Andrea Cancela da Cruz-Kaled; Giovanni Roriz Lyra Hillebrand (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– Being the most inhospitable continent in Earth, Antarctica has more than 90% of its territory covered with ice and contains around 70% of all drinkable water in the world. Its proximity to South America turns this region into especially relevant to Brazil, being included to the country's strategic surrounding area. Furthermore, Antarctica is prominent for being administered through an international regime based on a system of conventions and documents, which defined research activities as its fundamental purpose. The objective of this paper is to present the aspects of Brazilian Antarctic Program (PROANTAR, in Portuguese), the main instrument of the national Antarctic policy and the country's continued presence in the continent. In addition, this work aims to depict the importance of Antarctic activities to Brazil, considering not only strategic concerns, yet also their relevance to national scientific research. Finally, it investigates PROANTAR's budgetary elements, pointing out its current perspectives, and examines which directions the public policies should take to contribute to the program's continuity and strengthening.
Keywords: F50; F53; Q50; Q55; 330; Antarctica; Brazilian Antarctic Program; research and development (R&D); strategic surrounding area; geopolitics; maritime power